Ascorbic acid-induced warfarin resistance after breast cancer surgery: a case report and literature review - Gao, Pingfa; Shen, Yang; Wu, Ping; Lv, Wenjie (Frontiers in Pharmacology, 2024)
Warfarin is an anticoagulant that requires INR-based dosage adjustment. Ascorbic acid may impair warfarin effectiveness according to limited literature. We report a rare case of a 63-year-old woman with an aortic valve replacement history who developed warfarin resistance after taking ascorbic acid for anemia following breast cancer surgery. Despite increasing the warfarin dose from 6 mg to 10 mg daily, her INR remained below the therapeutic range. After ruling out other causes of warfarin resistance, we discontinued ascorbic acid and observed a rapid increase in INR to target values. The temporal relationship and the absence of other confounding factors confirmed the causality of ascorbic acid in this case. We recommend that patients concomitantly taking vitamin C and warfarin should monitor their INR values closely and discontinue ascorbic acid as soon as possible if they exhibit signs of warfarin resistance.